2020
DOI: 10.1183/23120541.00365-2020
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with reduced mortality after respiratory viral infection

Abstract: BackgroundSeveral studies suggest that statins, besides reducing cardiovascular disease, have anti-inflammatory properties which might provide a benefit in downregulating the immune response after a respiratory viral infection (RVI) and, hence, decreasing subsequent complications. We aim to analyse the effect of statins on mortality after RVI.MethodsA single-centre, observational and retrospective study was carried out including all adult patients with a RVI confirmed by PCR tests from October 2, 2017 to May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been demonstrated that statins significantly suppressed the activation of NF-κB and exert anti-inflammatory actions (10)(11)(12). Observational studies have reported that treatment with statins was associated with a reduced mortality rate in hospitalized patients with influenza (13). Previous studies have shown that statins may be also useful in the treatment of COVID-19 due to their pleotropic effect (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that statins significantly suppressed the activation of NF-κB and exert anti-inflammatory actions (10)(11)(12). Observational studies have reported that treatment with statins was associated with a reduced mortality rate in hospitalized patients with influenza (13). Previous studies have shown that statins may be also useful in the treatment of COVID-19 due to their pleotropic effect (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Statins, by virtue of their pleiotropic properties reduce pneumonia and ASCVD-related mortality [13][14][15][16][17] by modulating acute lung injury [18], neutrophil function [19], thrombosis [20], inflammation [21] and endothelial dysfunction [22]. Several studies [8,[23][24][25][26][27] have shown improvement in clinical outcomes from respiratory infections in statin users (Table 1).…”
Section: Introductionmentioning
confidence: 99%